Depressive symptoms among older adults with HIV in Namibia: the role of social support and spirituality. Issue 1 (2nd January 2021) - Kalomo, Eveline Ndinelao; Jun, Jung Sim; Lee, Kyoung Hag; Kaddu, Mgori Nuru
Abstract : Background: More than 60% of older adults living with HIV reside in sub-Saharan Africa. Namibia has one of the highest HIV/AIDS prevalence rates. This study examined the association between social support, spirituality and depressive symptoms. Method and results: The sample consisted of 147 Oshiwambo-speaking older adults (mean age = 61 years, SD = 6.92 years) with HIV in Namibia. By utilising a hierarchical multivariate regression method, this study found that social support from friends and spirituality showed a significant negative relationship to depressive symptoms. In addition, self-rated health status and alcohol use were significant sociodemographic predicitive factors of depressive symptoms. Conclusion : This study suggests the need to develop interventions and support programmes that incorporate peer support and spiritual practice to promote health and well-being among older persons living with HIV in Namibia.